Shark Saver Malaysia / Puteri Alya Batrisyia Hamdan - Hamdan, Puteri Alya Batrisyia (2022)
Shark Savers Malaysia SSMY is a non-profit volunteer led initiative dedicated to saving sharks through building awareness, education and grassroots action. SSMY was formed in 2013 and registered under the registry of societies Malaysia in 2016. They are a group of like minded people from various communities who share the obsession of making the world a better place.